MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MENCORET DENGAN KRAYON PADA ANAK DOWN SYNDROME DI WISMA BHAKTI LUHUR MALANG - Maria Vianti Desa; Selfiana Amfotis (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2022)
Children with down syndrome experience various obstacles, such as fine motor and gross motor impairment. Gross motor and fine motor barriers will affect various daily activities even though they are very simple. Down syndrome children, motor skills are very low because their intelligence is also low. The low fine motor skills of children with down syndrome cause many obstacles. Fine motor barriers in the form of folding, colouring, drawing, painting, cutting, scraping and scribbling with crayons. The condition of fine motor skills in scribbling using crayons is very lacking, so it is necessary regularly. Fine motor skills are developed so that the ability to move small muscles is more mature in preparation to help children with down syndrome write. This study aims to prove that practising scribbling with crayons can improve fine motor skills in children with down syndrome. With this type of experimental design research used pre-experimental in the form of one group pretest-postest. The research was carried out at Wisma Bhakti Luhur consisting of 4 children with down syndrome. Based on the results obtained after being tread with scribbling with crayons for 4 children with down syndrome, there was an increase for JH, RZ in the practice of crossing out straight lines, crossing out upwards, crossing out downwards, crossing out siksak, crossing out, crossing out triangles, getting an average score of 12,5%. RL: crossing out a straight line, crossing out up, crossing out down, crossing out siksak, crossing out, crossing out triangles got an average score of 15%. Meanwhile SN: crossing out a straight line, crossing out up, crossing out down, crossing out siksak, crossing out, crossing out triangles got an average score of 32,5%.